Back Cover: A Hybrid Catalyst for Light‐Driven Green Molecular Transformations (ChemPlusChem 1/2017). Issue 1 (24th October 2016) - Shimakoshi, Hisashi; Hisaeda, Yoshio
Abstract : The cover picture shows semiconductor–metal complex composites that are effective photocatalysts for both biomimetic and bioinspired reactions. Owing to the synergistic effect of both components in the B12 complex–titanium oxide hybrid catalyst, light‐driven molecular transformations can proceeded effectively. Details are given in the Minireview by H. Shimakoshi and Y. Hisaeda onpage 18 in Issue 1, 2017 (DOI: 10.1002/cplu.201600303).